Ecological implications of variable energy storage in the keystone predator, Pisaster ochraceus - Carlos D. Robles; Mayra Molina; Carlos Alan Martinez; Luis Alvarez (Ecosphere, 2021)
Abstract We considered how environmental variation and adaption together constrain energy acquisition of a keystone predator and how the constraints might influence its ecological function. We tested the proposition that changing energy availability, occurring as shifts in shore level and size composition of the lower vertical boundary of intertidal mussel beds (Mytilus spp.), affects energy storage and growth of predatory sea stars, Pisaster ochraceus. Energy storage of Pisaster (mass of the pyloric caeca, PC) increased when highly variable inter‐annual mussel recruitment temporarily shifted the lower boundary of the mussel bed down‐shore; energy storage decreased when the lower boundary receded up‐shore. Greatest storage occurred during massive recruitment of juvenile mussels, which caused the largest downward extensions of the boundary. To test the causal basis of the storage–boundary correlation, sea stars collected from sites with natural episodes of massive mussel recruitment were tagged and translocated to sites with experimentally shifted boundaries. On mussel beds with lower boundaries artificially expanded downward, the sea stars sustained high energy storage over most of the range of initial sizes. On mussel beds left unaltered or experimentally recessed, they lost PC mass. The amounts of loss were similar between unaltered and recessed treatments. We suggest an explanation for this unexpected similarity. Pisaster aggregate and disperse in response to the inter‐annual variation in mussel recruitment, and this numerical response is integral to mechanisms holding stationary the lower boundary, imposing stability on the local mussel population. Inter‐annual episodes of massive mussel recruitment, which have the potential to abruptly destabilize the lower boundaries, (1) elicit the strongest numerical response and (2) incur the greatest energy storage. The amount of energy storage in the season of active foraging is approximately proportional to the reproductive output in the subsequent reproductive season. Therefore, we propose that the system property of prey population stability originates in energy constraints underpinning Darwinian fitness of a keystone predator. Study limitations and further tests of the hypothesis are described.